Studies in Cassite History and Archaeology - Carter, Theresa Howard (1962)
Ph. D.; University Microfilms Order No. 64-8228. Microfilm $4.85; Xerography $17.10; See: Dissertation Abstracts 25/3 (Ann Arbor, Mich., September 1964) 1868.